2022
DOI: 10.3390/agriculture12070962
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Nitrogen Application Leads to Lower Rice Yield and Grain Quality by Inhibiting the Grain Filling of Inferior Grains

Abstract: Nitrogen fertilizer is an important agronomic measure to regulate rice yield and grain quality. Grain filling is crucial for the formation of rice yield and grain quality. However, there are few studies on the effects of excessive nitrogen application (ENA) on grain filling rate and grain quality. A two-year field experiment was conducted to reveal the difference in grain filling characteristics and grain quality of superior grains (SG) and inferior grains (IG), as well as their responses to nitrogen fertilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…We observed in our field trials that over‐expression of Nhd1 altered heading date but not mature time at the same N condition, implying the different grain filling period of Nhd1 over‐expression lines and WT (Figure 1). Limited N supply can promote filling rate but reduce its stage duration which in turn deteriorate grain quality with high AC (Zhang et al ., 2021b; Zhao et al ., 2022). Indeed, we detected the similar results in WT (Figures 1e and 4a).…”
Section: Discussionmentioning
confidence: 99%
“…We observed in our field trials that over‐expression of Nhd1 altered heading date but not mature time at the same N condition, implying the different grain filling period of Nhd1 over‐expression lines and WT (Figure 1). Limited N supply can promote filling rate but reduce its stage duration which in turn deteriorate grain quality with high AC (Zhang et al ., 2021b; Zhao et al ., 2022). Indeed, we detected the similar results in WT (Figures 1e and 4a).…”
Section: Discussionmentioning
confidence: 99%
“…However, N supply was found up to 0.3 or 0.375 g kg -1 soil, and the FW, DW accumulation rate, and N uptake rate did not increase with increasing N application. Increasing N application decreases the N contents at a certain point and causes a decline in the yields of horticultural crops ( Zhao et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…After that, it sharply decreased. It indicates that excess N reduced rice fertility, which ultimately negativelyimpacted achieving higherrice yields (Zhao et al, 2022). It was found that 90 kg N ha -1 (100% recommended rate) treatment had 80% higher grain production over control.…”
Section: Growth and Yield Attributing Charactersmentioning
confidence: 99%